Preparation of solid electrolyte and solid-state battery thereof
By preparing and coating solid electrolyte slurry in solid state batteries, the problems of stable homogeneity and thickness reliability of solid electrolyte layer in solid state batteries are solved, and a solid state battery with high energy density, high safety and environmental protection are achieved.
Patent Information
- Application Number
- CN202411590761.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art is difficult to ensure the stable homogeneity and thickness reliability of the solid electrolyte layer at room temperature, resulting in poor safety and consistency of solid-state batteries.
By preparing a solid electrolyte slurry and uniformly coated on the surface of the positive electrode sheet by a coating machine at room temperature, a solid electrolyte layer with a stable, homogeneous and reliable thickness is formed.
It is achieved to form a solid electrolyte layer with stable homogeneity and reliable thickness under normal temperature environment, which improves the safety and consistency of solid-state batteries. At the same time, the solid electrolyte and separator are removed, and the mass energy density is increased by about 28%.
Smart Images

Figure CN119447432A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to preparation of a solid electrolyte and a solid-state battery thereof. Background Art
[0002] Under low temperature conditions, the performance of traditional liquid batteries will decline due to increased electrolyte viscosity, reduced conductivity, increased electrolyte / electrode interface impedance and charge transfer impedance, and reduced lithium ion migration rate. Solid electrolyte batteries do not have the problem of electrolyte solidification at low temperatures. At the same time, they are less affected by high temperature conditions and have high safety. Therefore, they have a larger operating temperature range and are significantly better than liquid batteries.
[0003] The existing patent CN117239216A proposes to encapsulate the positive electrode, negative electrode and solid electrolyte solution in a shell, and obtain an all-solid-state lithium-ion battery through in-situ polymerization and curing. Although this method is relatively efficient, it cannot guarantee that a stable, homogeneous and reliable thickness solid electrolyte layer can be formed between the positive and negative electrodes, and has poor safety and consistency.
[0004] In the existing patent CN111509186B, the solid electrolyte coating slurry is solid at room temperature and forms a gas at 60-200°C. While heating, pressure is applied to the surface of the positive electrode current collector forming the solid electrolyte coating to compact the positive electrode of the lithium-ion solid-state battery. This method also cannot ensure that a stable, homogeneous, and reliable thickness electrolyte layer can be formed on the positive electrode surface. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a solid electrolyte and a solid-state battery thereof, so as to solve the above-mentioned defects caused by the prior art.
[0006] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a solid-state battery, in which a positive electrode sheet, a solid electrolyte, and a negative electrode sheet are assembled by stacking, and a solid-state battery can be obtained without injecting an electrolyte.
[0007] Preferably, the positive electrode sheet, the solid electrolyte, and the negative electrode sheet are assembled by winding, and a solid-state battery can be produced without injecting an electrolyte.
[0008] A method for preparing a positive electrode sheet comprises the following steps:
[0009] S1. Weigh 90-99% of the total weight of the powder, the positive electrode active material, 1-5% binder A, 1-5% binder B, 1-5% conductive agent, stir and mix for 0.5-1h, the speed is 500-1000r / min, the stirring temperature is 10-60°C, and mix evenly;
[0010] S2. Add 44% of the total weight of the cathode solvent, 0.1-1% of the dispersant, and 0.5-2% of the conductive agent to the material obtained in S1, and stir and mix for 0.5-2h at a speed of 500-2000r / min and a stirring temperature of 10-60°C;
[0011] S3. Add 6% of the total weight of the cathode solvent to the material obtained in S2, stir and mix for 0.5-5h, at a speed of 1000-3000r / min and a stirring temperature of 10-60°C to obtain a cathode electrode slurry;
[0012] S4. The slurry obtained in step S3 is uniformly coated on the current collector at 10-120° C. by a coating machine to obtain an active material sheet with a thickness of 100-300 μm, and then rolled to obtain a positive electrode sheet with a thickness of 50-200 μm.
[0013] A method for preparing a negative electrode sheet comprises the following steps:
[0014] S5. Weigh 90-99% of the total weight of the powder, the negative electrode active material, 0-2% thickener A, 1-5% conductive agent, stir and mix for 0.5-1h, the speed is 500-1000r / min, the stirring temperature is 10-60 ℃, and mix evenly;
[0015] S6. Add 40% of the total weight of the negative electrode solvent to the material obtained in S5 and stir and mix for 0.5-2h at a speed of 500-1000r / min and a stirring temperature of 10-60°C;
[0016] S7. Add 40% of the total weight of the negative electrode solvent and 1-5% of the binder A to the material obtained in S6 and stir and mix for 0.5-5h at a speed of 500-2000r / min and a stirring temperature of 10-60°C to obtain a negative electrode slurry;
[0017] S8. The slurry obtained in step S7 is uniformly coated on the current collector at 10-110° C. by a coating machine to obtain an active material sheet with a thickness of 100-200 μm, and then rolled to obtain a negative electrode sheet with a thickness of 50-150 μm.
[0018] A method for preparing a solid electrolyte comprises the following steps:
[0019] S9. Weigh 50-95% of the total weight of the powder oxide solid electrolyte, 1-5% binder A, 1-5% conductive agent, stir and mix for 0.5-1h, the speed is 500-1000r / min, the stirring temperature is 10-60 ℃, and mix evenly;
[0020] S10. Add 70% of the total weight of the cathode solvent to the material obtained in S9, stir and mix for 0.5-5h, at a speed of 1000-3000r / min and a stirring temperature of 10-60°C to obtain a solid electrolyte slurry;
[0021] S11. The slurry obtained in step S10 is evenly coated on the obtained positive electrode sheet at 10-90° C. by a coating machine, and the thickness of a single layer coating is 0.5-10 um, so as to obtain a solid electrolyte layer located on the positive electrode sheet.
[0022] Preferably, the positive electrode active material includes one or more of lithium iron phosphate, lithium cobalt oxide, lithium iron manganese phosphate, and ternary materials, the binder A and the binder B are selected from one or more of polyvinylidene fluoride, polytetrafluoroethylene, acrylic resin, and styrene-butadiene rubber, and the dispersant includes one or two of polyvinyl pyrrolidone PVP and hexadecyltrimethylammonium bromide CTAB.
[0023] Preferably, the negative electrode active material includes one or more of graphite, silicon oxide, and silicon carbon, and the thickener is one or more of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose.
[0024] Preferably, the oxide solid electrolyte is one or more of Li7La3Zr2O12, Li5La3Nb2O12, Li7La3Sn2O12, and Li5La3Ta2O12.
[0025] Preferably, the battery includes any one of a liquid lithium-ion battery, a lithium-sulfur battery, a lithium-air battery, a solid-liquid hybrid lithium battery or an all-solid-state lithium battery.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The present invention discloses an oxide-oriented solid electrolyte and a solid-state battery. The positive electrode sheet of the solid-state battery includes a positive electrode current collector and a solid electrolyte layer. The solid electrolyte layer is made of various percentages of raw materials verified by experiments. The solid electrolyte slurry is first prepared and then coated on the surface of the positive electrode sheet. This ensures that a stable, homogeneous and reliable thickness solid electrolyte layer can be formed under normal temperature.
[0028] 2. This method removes the solid electrolyte and separator that account for about 20% of the battery weight, and the mass energy density is increased by about 28%. It not only has the characteristics of high energy density and high safety, but also has the advantages of high ionic conductivity, environmental protection and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The figure is a flow chart for preparing the solid electrolyte of the present invention. DETAILED DESCRIPTION
[0030] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.
[0031] See also Figure 1 The present invention provides a technical solution: a solid-state battery, in which a positive electrode sheet, a solid electrolyte, and a negative electrode sheet are assembled by stacking, and a solid-state battery can be obtained without injecting an electrolyte.
[0032] In this embodiment, the positive electrode sheet, the solid electrolyte, and the negative electrode sheet are assembled by winding, and a solid-state battery can be obtained without injecting an electrolyte.
[0033] A method for preparing a positive electrode sheet, the preparation of the positive electrode sheet comprising the following steps:
[0034] S1. Weigh 90-99% of the total weight of the powder, the positive electrode active material, 1-5% binder A, 1-5% binder B, 1-5% conductive agent, stir and mix for 0.5-1h, the speed is 500-1000r / min, the stirring temperature is 10-60°C, and mix evenly;
[0035] S2. Add 44% of the total weight of the cathode solvent (the overall solid content is about 75%), 0.1-1% of the dispersant, and 0.5-2% of the conductive agent to the material obtained in S1, and stir and mix for 0.5-2h at a speed of 500-2000r / min and a stirring temperature of 10-60°C;
[0036] S3. Add 6% of the total weight of the cathode solvent (the overall solid content is about 64%) to the material obtained in S2, stir and mix for 0.5-5h, the speed is 1000-3000r / min, and the stirring temperature is 10-60°C to obtain a cathode electrode slurry;
[0037] S4. The slurry obtained in step S3 is uniformly coated on the current collector at 10-120° C. by a coating machine to obtain an active material sheet with a thickness of 100-300 μm, and then rolled to obtain a positive electrode sheet with a thickness of 50-200 μm.
[0038] A method for preparing a negative electrode sheet, the preparation of the negative electrode sheet comprising the following steps:
[0039] S5. Weigh 90-99% of the total weight of the powder, the negative electrode active material, 0-2% thickener A, 1-5% conductive agent, stir and mix for 0.5-1h, the speed is 500-1000r / min, the stirring temperature is 10-60 ℃, and mix evenly;
[0040] S6. Add 40% of the total weight of the negative electrode solvent (the overall solid content is about 68%) to the material obtained in S5 and stir and mix for 0.5-2h at a speed of 500-1000r / min and a stirring temperature of 10-60°C;
[0041] S7. Add 40% of the total weight of the negative electrode solvent (the overall solid content is about 68%) and 1-5% of the binder A to the material obtained in S6, and stir and mix for 0.5-5h at a speed of 500-2000r / min and a stirring temperature of 10-60°C to obtain a negative electrode slurry;
[0042] S8. The slurry obtained in step S7 is uniformly coated on the current collector at 10-110° C. by a coating machine to obtain an active material sheet with a thickness of 100-200 μm, and then rolled to obtain a negative electrode sheet with a thickness of 50-150 μm.
[0043] A method for preparing a solid electrolyte, the preparation of the solid electrolyte comprising the following steps:
[0044] S9. Weigh 50-95% of the total weight of the powder oxide solid electrolyte, 1-5% binder A, 1-5% conductive agent, stir and mix for 0.5-1h, the speed is 500-1000r / min, the stirring temperature is 10-60 ℃, and mix evenly;
[0045] S10. Add 70% of the total weight of the cathode solvent (the overall solid content is about 60%) to the material obtained in S9, stir and mix for 0.5-5h, the speed is 1000-3000r / min, and the stirring temperature is 10-60°C to obtain a solid electrolyte slurry;
[0046] S11. The slurry obtained in step S10 is evenly coated on the obtained positive electrode sheet at 10-90° C. by a coating machine, and the thickness of a single layer coating is 0.5-10 um, so as to obtain a solid electrolyte layer located on the positive electrode sheet.
[0047] In this embodiment, the positive electrode active material includes one or more of lithium iron phosphate, lithium cobalt oxide, lithium iron manganese phosphate, and ternary materials, the binder A and the binder B are selected from one or more of polyvinylidene fluoride, polytetrafluoroethylene, acrylic resin, and styrene-butadiene rubber, and the dispersant includes one or two of polyvinyl pyrrolidone PVP and hexadecyltrimethylammonium bromide CTAB.
[0048] In this embodiment, the negative electrode active material includes one or more of graphite, silicon oxide, and silicon carbon, and the thickener is one or more of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose.
[0049] In this embodiment, the oxide solid electrolyte is one or more of Li7La3Zr2O12, Li5La3Nb2O12, Li7La3Sn2O12, and Li5La3Ta2O12.
[0050] In this embodiment, the battery includes any one of a liquid lithium-ion battery, a lithium-sulfur battery, a lithium-air battery, a solid-liquid hybrid lithium battery or an all-solid-state lithium battery.
[0051] Note that steps S9, S10, and S11 cannot be replaced arbitrarily. The solid electrolyte is added first because the solid electrolyte material is fully contacted with the binder and the conductive agent by adding the split dry mix first. The solvent added then mainly plays the role of lubrication and dispersion.
[0052] The following embodiments relate to a method for preparing a solid electrolyte by a dry process; in terms of weight percentage of the total weight of the powder, the examples of the solid electrolyte are as follows:
[0053] Example 1
[0054] A, 70wt% solid electrolyte, 25wt% conductive agent, 5wt% binder B;
[0055] Example 2
[0056] B, 80wt% solid electrolyte, 15wt% conductive agent, 5wt% binder B;
[0057] Example 3
[0058] C, 90wt% solid electrolyte, 5wt% conductive agent, 5wt% binder B;
[0059] Example 4
[0060] D, 95wt% solid electrolyte, 0wt% conductive agent, 5wt% binder B;
[0061] Example 5
[0062] E, 93wt% solid electrolyte, 2wt% conductive agent, 5wt% binder B;
[0063] Example 6
[0064] F, 95wt% solid electrolyte, 5wt% conductive agent, 0wt% binder B;
[0065] Solid electrolyte preparation:
[0066] 1. The slurry prepared above is evenly coated on the positive electrode sheet at 70-90°C by a coating machine, with a single layer coating thickness of 0.5-10um to obtain a sheet with a thickness of 50-220μm;
[0067] 2. Roll the obtained flakes to form 50-215 μm flakes;
[0068] Lithium battery preparation:
[0069] The positive electrode sheets (including the solid electrolyte coating) of different embodiments are respectively assembled with the same negative electrode sheet, separator and electrolyte to form a battery.
[0070] Table 1 Peel strength, membrane resistance and battery DC internal resistance (DCR) data after solid electrolyte is made:
[0071]
[0072] As can be seen from Table 1, Example 5 among the preparations of Examples 1-6 of the present invention shows better peel strength, film resistance and DCR.
[0073] It is known from common technical knowledge that the present invention can be implemented by other embodiments that do not deviate from its spirit or essential features. Therefore, the above disclosed embodiments are only illustrative in all respects and are not exclusive. All changes within the scope of the present invention or within the scope equivalent to the present invention are included in the present invention.
Claims
1. A solid-state battery, characterized in that: The positive electrode sheet, solid electrolyte, and negative electrode sheet are assembled by stacking, and a solid-state battery can be produced without injecting electrolyte.
2. A solid-state battery according to claim 1, characterized in that: The positive electrode sheet, solid electrolyte, and negative electrode sheet are assembled by winding, and a solid-state battery can be produced without injecting electrolyte.
3. A solid-state battery according to claim 2, characterized in that: The preparation of the positive electrode sheet comprises the following steps: S1. Weigh 90-99% of the total weight of the powder, the positive electrode active material, 1-5% binder A, 1-5% binder B, 1-5% conductive agent, stir and mix for 0.5-1h, the speed is 500-1000r / min, the stirring temperature is 10-60°C, and mix evenly; S2. Add 44% of the total weight of the cathode solvent (the overall solid content is about 75%), 0.1-1% of the dispersant, and 0.5-2% of the conductive agent to the material obtained in S1, and stir and mix for 0.5-2h at a speed of 500-2000r / min and a stirring temperature of 10-60°C; S3. Add 6% of the total weight of the cathode solvent (the overall solid content is about 64%) to the material obtained in S2, stir and mix for 0.5-5h, the speed is 1000-3000r / min, and the stirring temperature is 10-60°C to obtain a cathode electrode slurry; S4. The slurry obtained in step S3 is uniformly coated on the current collector at 10-120° C. by a coating machine to obtain an active material sheet with a thickness of 100-300 μm, and then rolled to obtain a positive electrode sheet with a thickness of 50-200 μm.
4. A solid electrolyte according to claim 2, characterized in that: The preparation of the negative electrode sheet comprises the following steps: S5. Weigh 90-99% of the total weight of the powder, the negative electrode active material, 0-2% thickener A, 1-5% conductive agent, stir and mix for 0.5-1h, the speed is 500-1000r / min, the stirring temperature is 10-60 ℃, and mix evenly; S6. Add 40% of the total weight of the negative electrode solvent (the overall solid content is about 68%) to the material obtained in S5 and stir and mix for 0.5-2h at a speed of 500-1000r / min and a stirring temperature of 10-60°C; S7. Add 40% of the total weight of the negative electrode solvent (the overall solid content is about 68%) and 1-5% of the binder A to the material obtained in S6, and stir and mix for 0.5-5h at a speed of 500-2000r / min and a stirring temperature of 10-60°C to obtain a negative electrode slurry; S8. The slurry obtained in step S7 is uniformly coated on the current collector at 10-110° C. by a coating machine to obtain an active material sheet with a thickness of 100-200 μm, and then rolled to obtain a negative electrode sheet with a thickness of 50-150 μm.
5. A solid-state battery according to claim 2, characterized in that: The preparation of the solid electrolyte comprises the following steps: S9. Weigh 50-95% of the total weight of the powder oxide solid electrolyte, 1-5% binder A, 1-5% conductive agent, stir and mix for 0.5-1h, the speed is 500-1000r / min, the stirring temperature is 10-60 ℃, and mix evenly; S10. Add 70% of the total weight of the cathode solvent (the overall solid content is about 60%) to the material obtained in S9, stir and mix for 0.5-5h, the speed is 1000-3000r / min, and the stirring temperature is 10-60°C to obtain a solid electrolyte slurry; S11. The slurry obtained in step S10 is evenly coated on the obtained positive electrode sheet by a coating machine at 10-90° C., and the thickness of a single layer coating is 0.5-10 um, so as to obtain a solid electrolyte layer located on the positive electrode sheet.
6. A method for preparing a positive electrode sheet according to claim 3, characterized in that: The positive electrode active material includes one or more of lithium iron phosphate, lithium cobalt oxide, lithium iron manganese phosphate, and ternary materials; the binder A and the binder B are selected from one or more of polyvinylidene fluoride, polytetrafluoroethylene, acrylic resin, and styrene-butadiene rubber; and the dispersant includes one or two of polyvinyl pyrrolidone PVP and hexadecyltrimethylammonium bromide CTAB.
7. A method for preparing a negative electrode sheet according to claim 4, characterized in that: The negative electrode active material includes one or more of graphite, silicon oxide, and silicon carbon, and the thickener is one or more of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose.
8. A method for preparing a solid electrolyte according to claim 5, characterized in that: The oxide solid electrolyte is one or more of Li7La3Zr2O12, Li5La3Nb2O12, Li7La3Sn2O12, and Li5La3Ta2O12.
9. A solid-state battery according to claim 2, characterized in that: The battery includes any one of a liquid lithium ion battery, a lithium sulfur battery, a lithium air battery, a solid-liquid hybrid lithium battery or an all-solid lithium battery.